Religie en het maatschappelijke midden in Nederland - René Bekkers (Religie & Samenleving)
The civic core is the part of the population that is responsible for a disproportionately large part of civic participation. This paper shows how the level of activity and the composition of the civic core have changed in the Netherlands between 1997 and 2009 using data from the Giving in the Netherlands Survey. The results show that – despite ongoing secularization – the civic core in the Netherlands is increasingly religious. At the same time, the prevalence of higher educated individuals in the civic core has diminished. Engagement in charitable giving is increasingly related to engagement in volunteering. In sum, the increasing concentration of activity in the civic core is especially visible among religious persons and volunteers.